Spectroscopic Studies of Magnetron Sputtering Plasma Discharge in Cu/O2/Ar Mixture for Copper Oxide Thin Film Fabrication - Ahmad Faizal, Mohd Zain; Jia, Wei Low; Nafarizal, Nayan; Mohd Zainizan, Sahdan; Mohd Khairul, Ahmad; Ali Yeon, Md Shakaff; Ammar, Zakaria (Penerbit Universiti Teknologi Malaysia, 2015)
Magnetron sputtering plasma for the deposition of copper oxide thin film has been investigated using optical emission spectroscopy and Langmuir probe. The intensity of the light emission from atoms and radicals in the plasma were measured using optical emission spectroscopy (OES). Then, Langmuir probe was employed to estimate the plasma density, electron temperature and ion flux. In present studies, reactive copper sputtering plasmas were produced at different oxygen flow rate of 0, 4, 8 and 16 sccm.The size of copper target was 3 inches. The dissipation rf power, Ar flow rate and working pressure were fixed at 400 W, 50 sccm and 22.5 mTorr, respectively. Since the substrate bias plays an important role to the thin film formation, the substrate bias voltages of 0, -40, -60 and -100 V were studied. Based on OES results, oxygen emission increased drastically when the oxygen flow rate above 8 sccm. On the other hand, copper and argon emission decreased gradually. In addition, Langmuir probe results showed a different ion flux when substrate bias voltage was applied. Based on these plasma diagnostic results, it has been concluded that the optimized parameter to produce copper oxide thin film are between -40 to - 60 V of substrate bias voltage and between 8 to 12 sccm of oxygen flow rate